2022
DOI: 10.3390/ijerph19042158
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Identification of Emotional Neural State Evoked by Virtual Environment Interaction

Abstract: Classifying emotional states is critical for brain–computer interfaces and psychology-related domains. In previous studies, researchers have tried to identify emotions using neural data such as electroencephalography (EEG) signals or brain functional magnetic resonance imaging (fMRI). In this study, we propose a machine learning framework for emotion state classification using EEG signals in virtual reality (VR) environments. To arouse emotional neural states in brain signals, we provided three VR stimuli scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The authors indicated that one benefit of using EEG signals in related studies is their great temporal resolution, which can reach the millisecond level. Additionally, more recent EEG collection devices have received favorable assessments for clinical and real-world BMI use in terms of signal dependability and mobility (Jung et al 2022). In addition to assisting in the diagnosis of brain tumors from electroencephalography (EEG), the study of brain waves also aided in the treatment of intellectual deficiencies, including Alzheimer's disease, sleep disorders, and pilot tiredness.…”
Section: Introductionmentioning
confidence: 99%
“…The authors indicated that one benefit of using EEG signals in related studies is their great temporal resolution, which can reach the millisecond level. Additionally, more recent EEG collection devices have received favorable assessments for clinical and real-world BMI use in terms of signal dependability and mobility (Jung et al 2022). In addition to assisting in the diagnosis of brain tumors from electroencephalography (EEG), the study of brain waves also aided in the treatment of intellectual deficiencies, including Alzheimer's disease, sleep disorders, and pilot tiredness.…”
Section: Introductionmentioning
confidence: 99%
“…Seizing these tools and creating personalized experiences either with a headset or on a screen can improve the user’s engagement, aiding his/her in achieving more challenging targets [ 25 ]. Multiple techniques range from machine learning [ 26 ] to multimodal frameworks [ 24 ] to classify the emotional states based on EEG and other sensors. This study’s objective was to analyze patients’ affective states during RAGT to determine under which conditions the measurement is accurate and can be used to create a dynamic feedback-based VR environment to improve the efficiency of the sessions.…”
Section: Introductionmentioning
confidence: 99%